GAMBARAN TEKANAN PANAS PADA LINGKUNGAN KERJA DAPUR KATERING DI KOTA DENPASAR - Utami, Ariqah Dhiya; Ariastuti, Ni Luh Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p23, 2025)
Kitchen is a work environment that is directly related to heat stress due to cooking activities. A hot work environment can make the kitchen uncomfortable and create disease in workers. This study aims to describe the heat stress and the characteristics of the work environment at catering kitchens in Denpasar City. The study used a quantitative descriptive, the sample in this study amounted to 25 catering used sampling technique accidental sampling. Heat stress was calculated using wet bulb temperature index calculation by measuring the temperature at two different times. The characteristics of the catering kitchen environment was seen using an observation checklist and to describe the heat stress risk map was used ArcGIS app. The highest heat pressure was found in the second measurement with an average temperature of 30.14?C which is included in the high heat category. Catering kitchen characteristics such as kitchen area and room temperature control are indicators of increasing temperature in the work environment. Evidence suggests that all kitchens during peak periods exhibit heat stress levels that exceed established limits. Therefore, it is very important for business entities and policy makers to allocate focus on optimizing kitchen facilities, including the kitchen area and room temperature regulation. Keyword: Heat Pressure, Work Environment, Denpasar City Catering